Effect of establishment methods and varieties on yield attributes, yield and economics of rice in submergence prone lowland of Eastern India - Das, Mishan; Singh, U.P.; Meena, Rajendra Prasad; Pradhan, Surajyoti; Hingonia, Kiran (Annals of Agricultural Research, 2019)
A field study was undertaken to evaluate the establishment methods, and varieties on yield and economics in submergence prone rainfed lowland situation at agriculture farm of Institute of Agricultural Sciences, Banaras Hindu University, Varanasi, India during kharif seasons of 2014. The experiment was laid out in split plot design and replicated thrice with four crop establishment methods in main plot along with two rice varieties (swarna-sub1 and samba mahsuri-sub1)in sub plot. Remarkable effects were noted under establishment methods and rice verities in terms of yield attributes, yield and economics. The highest yield attributes [panicle/m2 (282), panicle length (23.2 cm), panicle weight (3.4g), grain/panicle (135) and test weight (19.8g)], grain yield (5.1t/ha), biological yield (11.7 t/ha), net returns (` 57.4Ã—103/ha) and B:C (1.47) were recorded with DSR-ZT drill seeding with Sesbania co-culture (brown manuring). Similarly, Swarna-sub1 reported superior to Samba mahsuri-sub1in terms of yield and economics.